Mitochondria-Targeting Chemodynamic Therapy Nanodrugs for Cancer Treatment - Chen, Qiaohui; Li, Niansheng; Wang, Xiaoyuan; Yang, Yuqi; Xiang, Yuting; Long, Xingyu; Zhang, Jinping; Huang, Jia; Chen, Li; Huang, Qiong (Frontiers in Pharmacology, 2022)
Mitochondria, as one of the most critical subcellular organelles of cancer cells, are very vulnerable and often on the verge of oxidative stress. The classic chemodynamic therapy (CDT) directly employs endogenous chemical energy to trigger reactive oxygen radicals (ROS) burst and destroy tumor cells. However, the effectiveness of CDT is restricted by the limited diffusion distance and short half-life of ROS. From this perspective, the treatment method (mitochondria-targeting chemodynamic therapy nanodrugs, M-CDT nanodrugs) that can generate high levels of ROS at the mitochondrial site is extremely efficient and promising for cancer treatment. Currently, many emerging M-CDT nanodrugs have been demonstrated excellent spatial specificity and anti-cancer efficacy. In this minireview, we review various proof-of-concept researches based on different M-CDT nanodrugs designs to overcome the limits of the efficacy of CDT, mainly divided into four strategies: supplying H2O2, non-H2O2 dependent CDT, eliminating GSH and enhancing by hyperthermia therapy (HT). These well-designed M-CDT nanodrugs greatly increase the efficacy of CDT. Finally, the progress and potential of M-CDT nanodrugs are discussed, as well as their limitations and opportunities.